Ларвальные и постларвальные сегменты головы насекомых - Пучкова, Л.В. (Вестник зоологии, 1972)
The head of insects is a result of integration of primary radial endonal structures — derivatives of aboral complex of Ctenophora type ancestors of oligomerous organisms with three larval and five postlarval segments. The nervous apparatus of the larval segments is a derivative of the primary radial eight-ray orthogon, the ganglia of which appeared in the points of radial stems' intersection with circumblastopoṙal ring, groupped in pairs and laid the basis of four primary methameres. Three of them after distinguishment oi the proliferation zone remained at the front end of the body. Two of them are primary preoral. The neuromere of the former is rudimentary and might be involved into the composition of the frontal ganglion, the neuromere of the latter was involved into the composition of the archecerebrum as optical ganglia. The coeloms of these segments disappeared at very early stages of phylogenesis. The nervous apparatus of the third larval segment completed a protocerebral division of the brain as ventral bodies. A seeming development of ventral bodies and some endonal structures of the brains from one embryonal anlage is a result of development by the archallaxis type. The antennular segment is postlarval, but, as well as some segments which are behind, is secondary larvalized.